2014
DOI: 10.1111/pirs.12013
|View full text |Cite
|
Sign up to set email alerts
|

Serving regional demand in facility location

Abstract: Location modelling is employed in urban and regional planning to site facilities that provide services of some sort. Issues to be considered usually include the number of facilities to locate, where to site those facilities and how demand is to be served. Given the geographic nature of location problems, a key issue is how to represent facilities and demand in geographic space. Traditionally, spatial abstraction as discrete demand is assumed as it simplifies model formulation and reduces computational complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 63 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…An essential distinction of formulation (1)–(5) is that objective (1) is nothing other than the total weighted distance measure reflecting the intent of the classic Weber problem (see Church, 2019; Murray, 2018; Murray et al, 2020; Wesolowsky, 1993; Yao & Murray, 2014). Minimizing total weighted distance is equivalent to minimizing average distance and hence reflects the notion of access.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…An essential distinction of formulation (1)–(5) is that objective (1) is nothing other than the total weighted distance measure reflecting the intent of the classic Weber problem (see Church, 2019; Murray, 2018; Murray et al, 2020; Wesolowsky, 1993; Yao & Murray, 2014). Minimizing total weighted distance is equivalent to minimizing average distance and hence reflects the notion of access.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The caveat is that (X κ , Y κ ) can be found. Solving for each face Weber point (X κ , Y κ ) is possible using the unconstrained regional (classic) Weber point, X, Ŷ , which can be found using the iterative approach of Weiszfeld (see Schaefer & Hurter Jr, 1974;Church & Murray, 2009;Yao & Murray, 2014;Church, 2019;Murray et al, 2020;Murray, 2021). Since the classic Weber problem, (3), is convex, it is true that the optimal face Weber point (X κ , Y κ ) can be derived using the nearest point operatory,…”
Section: Formalization and Solutionmentioning
confidence: 99%
“…When applying basic calculus, however, its solution is more complicated. Weiszfeld () demonstrated that the derivative information could be used to devise an iterative solution scheme, where an initial guess at the best‐point center location could be systematically refined and improved, eventually converging to the optimum site (see also Church & Murray , Yao & Murray ). This solution method relies on the following simplified derivatives:Xt+1,Yt+1=i=1naixiXtxi2+Yty2i=1naiXtxi2+Yty2,i=1naiyiXtxi2+Yty2i=1naiXtxi2+Yty2…”
Section: Technical Specificationmentioning
confidence: 99%